Paciente masculino de 8 años con bronquitis aguda. - Avilés Villamarin, Carlos Manuel (2021)
The effectiveness of interventions for respiratory problems has been shown to be very important and, more importantly, highly trained and well-trained personnel who perform such procedures will greatly improve the health of the respiratory system. Patients: People with respiratory diseases. For example, in this case, acute bronchitis is a disease that seriously affects the population. The proportion of adults is higher and the proportion of children is lower, but it is not ruled out that they are also a vulnerable group. Acute bronchitis is a pathology that occurs when the bronchial tree becomes inflamed, usually caused by viruses or bacteria. Symptoms are cough, whitish or greenish sputum, mild shortness of breath, and noise when inhaling. For treatment, it is recommended to use prescription medications to hydrate or humidify the respiratory tract and bronchodilators to relax the bronchial muscles so that oxygen can flow properly.